Peran Masjid dalam Pengembangan Pendidikan Keagamaan Anak-Anak di Desa Talang Sebaris Kecamatan Air Periukan Kabupaten Seluma - Selvi Damaiyanti; Berliana Ayu; Ema Yurida; Marisa Sandika; Reni Novita; Ilma Ramadhani Putri; Jenni Rafflesia; Reno Renaldi; Yansen Paul (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The purpose of this study is to examine how mosques in Talang Sebaris Village, Air Periukan District, Seluma, contribute to children's religious education. In addition to being places of worship, mosques have significant social and educational roles in society, particularly in the development of children's religious understanding and character. This research examines several programs and activities started by mosques to encourage religious education, like children's recitations, Al-Qur'an Study Places (TPQ), and other religious activities. It does this using a qualitative approach using a case study method. Data was gathered through observation, interviews with parents, kids participating in these programs, and managers of the mosque. The study's findings indicate that Talang Sebaris Village's mosque has a big influence on how kids understand religion and morality. The success of these initiatives is, however, hampered by a lack of facilities and teaching personnel due to resource constraints. According to this research, mosques should get more community and governmental assistance in order to continue serving as hubs for longer-lasting and more efficient religious instruction.